Resistance of aerobic microorganisms and soil enzyme response to soil contamination with Ekodiesel Ultra fuel - Borowik, Agata; Wyszkowska, Jadwiga; Wyszkowski, Mirosław (Environmental science and pollution research international, 2017)
This study determined the susceptibility of cultured soil microorganisms to the effects of Ekodiesel Ultra fuel (DO), to the enzymatic activity of soil and to soil contamination with PAHs. Studies into the effects of any type of oil products on reactions taking place in soil are necessary as particular fuels not only differ in the chemical composition of oil products but also in the composition of various fuel improvers and antimicrobial fuel additives. The subjects of the study included loamy sand and sandy loam which, in their natural state, have been classified into the soil subtype 3.1.1 Endocalcaric Cambisols. The soil was contaminated with the DO in amounts of 0, 5 and 10 cm 3 kg −1 . Differences were noted in the resistance of particular groups or genera of microorganisms to DO contamination in loamy sand (LS) and sandy loam (SL). In loamy sand and sandy loam, the most resistant microorganisms were oligotrophic spore-forming bacteria. The resistance of microorganisms to DO contamination was greater in LS than in SL. It decreased with the duration of exposure of microorganisms to the effects of DO. The factor of impact (IF DO ) on the activity of particular enzymes varied. For dehydrogenases, urease, arylsulphatase and β-glucosidase, it had negative values, while for catalase, it had positive values and was close to 0 for acid phosphatase and alkaline phosphatase. However, in both soils, the noted index of biochemical activity of soil (BA) decreased with the increase in DO contamination. In addition, a positive correlation occurred between the degree of soil contamination and its PAH content.